Pendekatan pengembangan kurikulum humanistik, teknoligik dan rekontruksi sosial di MTs Negeri 1 Kota Malang - Rizqiyah, Naila Mazidah (Maliki Interdisciplinary Journal, 2024)
This study describes 1) the humanistic curriculum development approach, 2) the technological curriculum development approach, 3) the social reconstruction curriculum development approach in MTs Negeri 1 Malang City. This research is a research using qualitative methods that produce descriptive data from the research object observed in the form of written or spoken words. The results of this study indicate that 1) the humanistic curriculum is implemented well by teachers and parents who pay close attention to student learning processes and skills interests, such as conducting character building and discipline habituation programs and paying attention to student attitudes, 2) almost all learning and Administration is carried out using technological devices, both hardware and software. In the learning process at MTs Negeri 1 Malang City, one of them is using madrasah e-learning. The students are presented with material and assignments in the madrasah e-learning and from the madrasah e-learning students collect their assignments, so teachers can easily monitor directly between active students and students who are not active, 3) Application of the social reconstruction curriculum in MTs Negeri 1 Malang City, namely as a liaison between the school and local residents, during Eid al-Adha the school distributes sacrificial animals in the form of cows or goats from the contributions of school residents to local residents and the less fortunate, if there are children of local residents who want to go to school at MTs Negeri 1 Malang City, it will be facilitated through the selection stage, as well as on other holidays the MTs Negeri 1 Malang City school will participate with local residents.